Influence of Brief Psychoeducation Using Audio Video to Depression Score in Patients with Diabetic Foot Ulcer - Priyono, Djoko; Putri, Triyana Harlia; Fradianto, Ikbal; Yulanda, Nita Arisanti; Sukarni, Sukarni; Akhmad, Arif Nur (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Diabetes mellitus is one of the most common diseases today. It will cause several complications, one of which is a diabetic foot wound. The effects of this complication will affect psychological conditions in the form of depression. Depression can be handled using a psychosocial approach, one of which is psychoeducation intervention. The provision of psycho-educational interventions can use a variety of media so that the educational material presented is more attractive and can be received as much as possible. This study aimed to determine if there is an effect of brief psychoeducation using audio-video on depression score in a patient with a diabetic foot ulcer. This research used a quasi-experimental study with a pretest and posttest approach with the control group. The sample consisted of 32 respondents, divided into 2 groups of intervention and control groups. Samples were taken using purposive sampling. The instrument used was the Beck Depression Inventory (BDI) questionnaire. The data were analyzed using the Wilcoxon and Mann Whitney tests. The results showed that there was a difference in the average depression score between the control and intervention groups with a p-value less than 0.05. Psychoeducation using audio-video can help reduce depression in diabetic foot ulcer patients.Abstrak: Diabetes melitus merupakan salah satu penyakit yang paling banyak diderita saat ini. Diabetes melitus akan mengakibatkan terjadinya beberapa komplikasi, salah satunya luka kaki diabetik. Efek dari komplikasi ini akan mempengaruhi kondisi psikologis berupa depresi. Depresi dapat ditangani dengan menggunakan pendekatan psikososial, salah satunya intervensi psikoedukasi. Pemberian intervensi psikoedukasi dapat menggunakan berbagai media agar materi edukasi yang disampaikan lebih menarik dan dapat diterima semaksimal mungkin. Penelitian ini menggunakan kuasi eksperimen dengan pendekatan pretest and posttest with control group. Sampel berjumlah 32 responden, dibagi menjadi 2 kelompok intervensi dan kelompok control. Sampel diambil menggunakan purposive sampling. Instrumen yang digunakan adalah kuesioner Beck Depression Inventory (BDI). Data dianalisis menggunakan uji Wilcoxon dan Mann Whitney. Hasil menunjukkan bahwa terdapat perbedaaan rata-rata skor depresi antara kelompok kontrol dan intervensi dengan nilai p kurang dari 0,05. Psikoedukasi menggunakan video audio dapat membantu mengurangi depresi pada pasien diabetic foot ulcer.